Estudo fitoquímico e da atividade biológica de constituintes das raízes e galhos de Salacia crassifolia (Celastraceae) - Josana Pereira dos Santos (2019)
The phytochemical study of the roots and branches of Salacia crassifolia led to isolation of a betulin-betulinic acid mixture (SC19) and eighteen compounds: the sesquiterpene 9β, 10β-epoxy-3β-hydroxy-1βH,4βH,5βH,7βH,11αH-guaian-12,8β-olide (SC10); the steroids β-sitosterol (SC04) and 3-O-D-glycosyl-sitosterol (SC11); the flavonoid 4`-O-methylpigalocatechin (SC12); a cerebroside (SC13); the dimer caryopristimerin (SC03); the quinonemethides dispermoquinone (SC06), netzahualcoyonol (SC07), 20-hydroxy-20-epi-tingenone (SC08) and pristimerin (SC05); the aromatic triterpene 6-oxo-pristimerol (SC09); the ursane urs-12-ene-3β, 25,30-triol (SC02); the oleanane abruslactone A (SC01); the friedelane 21α-hidroxifriedelan-3-ona (SC16); the lupanes betulin (SC17), lupeol (SC14), lup-20(29)-en-2α,3β-diol (SC18) and lup-20(29)-en-3β,15α-diol (SC15). The chemical structures were determined by spectroscopic methods (IR, 1D and 2D NMR) and X-ray diffraction. SC10 and SC02 have not been described in the literature so far. The compounds SC03, SC05, SC08, SC09, SC12 (except for cytotoxicity), SC14, SC15, SC16, SC17 and SC18 were evaluated for acetylcholinesterase inhibition, in vitro cytotoxic activity and toxicity tests using the Caenorhabditis elegans model. All tested compounds inhibited acetylcholinesterase, and compounds SC03 (99±9%), SC08 (100±9%) and SC09 (99±8%) showed inhibition close to or greater than that of the eserine standard (94 ± 2%). The tested compounds showed low cytotoxicity against the THP-1 (acute myeloid leukemia cells), K562 (chronic myeloid leukemia cells) and MDA-MB-231 (mammary carcinoma cells) cancer cell lines in comparison with the standards. None of the tested compounds and extracts was toxic according to the C. elegans assay since the larvae survival rate in stage L1 was higher than 90%.